2016
DOI: 10.1242/jcs.194340
|View full text |Cite
|
Sign up to set email alerts
|

Transient fusion ensures granule replenishment to enable repeated release after IgE-mediated mast cell degranulation

Abstract: To ensure normal immune function, mast cells employ different pathways to release mediators. Here, we report a thus far unknown capacity of mast cells to recycle and reuse secretory granules after an antigen-evoked degranulation process under physiological conditions; this phenomenon involves the existence of a recycling secretory granule pool that is available for release in a short time scale. Rapid endocytic modes contributed to the recycling of ∼60% of the total secretory granule population, which involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 61 publications
(70 reference statements)
0
15
0
Order By: Relevance
“…The reason for the decline in supernatant levels of CRF and Ucn after 5 min of stimulation is unclear at this time but could represent a rapid reuptake or retrieval of CRF and Ucn by MCs. Released granule mediator recycling is known to occur rapidly after induction of exocytosis in MCs [52]. Interestingly, we found that CRF provide new insight into a potential mechanism, via CRF 1 , by which MC CRF receptor ligands are regulated.…”
Section: Discussionmentioning
confidence: 71%
“…The reason for the decline in supernatant levels of CRF and Ucn after 5 min of stimulation is unclear at this time but could represent a rapid reuptake or retrieval of CRF and Ucn by MCs. Released granule mediator recycling is known to occur rapidly after induction of exocytosis in MCs [52]. Interestingly, we found that CRF provide new insight into a potential mechanism, via CRF 1 , by which MC CRF receptor ligands are regulated.…”
Section: Discussionmentioning
confidence: 71%
“…The other possibility is that immediately after stimulation one or a few granules release their content via the ‘kiss and run’ mechanism and quickly SNAP-23 relocates with this granule. It has been reported earlier that MCs exhibit both ‘kiss and run’ and cavicapture types of transient granule-plasma membrane fusion to maintain their granularity and to retain the capacity of undergoing repeated exocytosis ( Balseiro-Gomez et al, 2016 ; Cohen et al , 2012). Further, a recent study involving atomic force microscopy (AFM) and transmission electron microscope (TEM) detailed the capture of a typical porosome on activated RBL mast cells, where membrane-bound secretory vesicles dock and fuse ( Deng et al, 2010 ; Jena, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…This physiological trigger initiates a cascade of events that results in the translocation, docking, and fusion of secretory granules with the plasma membrane leading to the release of inflammatory mediators stored in the secretory granules ( Galli et al, 2008 ; Puri and Roche, 2008 ). This process proceeds through a transient mechanism of fusion and release, called ‘kiss and run’, and cavicapture for a large proportion of granules in mast cells ( Balseiro-Gomez et al, 2016 ). Further, this secretion involves compound exocytosis where either the vesicles fuse with each other prior to plasma membrane fusion (multivesicular exocytosis) or in a sequential manner, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that degranulated MCs can recover and retain their ability to release the granular enzyme β-hexosaminidase and upregulate interleukin (IL)-6 and IL-13 gene expression on a second activation signal 24–48 hours later 25. In another study, maximal release of stored mediators occurred within minutes, and subsequent granule retrieval and recycling via rapid endocytosis resulted in the release of their contents within the scale of a few hours to days to maintain prompt secretory response on restimulation 26. In contrast to endocytic recycling, it is evident that the time needed for granule biogenesis, maturation and full MC recovery is much longer.…”
Section: Possible Underlying Immune Mechanismsmentioning
confidence: 97%